DISTRIBUTED OPERATIONS PLANNING IN THE LUMBER SUPPLY CHAIN: MODELS AND COORDINATION. - Gaudreault, Jonathan; Forget, Pascal; Frayret, Jean-Marc; Rousseau, Alain; Lemieux, Sebastien; D'Amours, Sophie (International Journal of Industrial Engineering: Theory, Applications and Practice, 2010)
Agent-based technology provides a natural approach to model supply chain networks. Each production unit, represented by an agent, is responsible for planning its operations and uses communication to coordinate with the others. In this paper, we study a softwood lumber supply chain made up of three production units (sawing unit, drying unit and finishing unit). We define the local problems and propose agent-specific mathematical models to plan and schedule operations. Then, in order to coordinate these plans between the three agents, we propose different coordination mechanisms. Incorporating these developments, we show how an agent-based simulation tool can be used to integrate planning models and evaluate different coordination mechanisms